(untitled) (Clinics, 2014)
OBJECTIVE: The purpose of this study was to examine the isovolumetric distribution kinetics of crystalloid fluid during cardiopulmonary bypass. METHODS: Ten patients undergoing coronary artery bypass grafting participated in this prospective observational study. The blood hemoglobin and the serum albumin and sodium concentrations were measured repeatedly during the distribution of priming solution (Ringer's acetate 1470 ml and mannitol 15% 200 ml) and initial cardioplegia. The rate of crystalloid fluid distribution was calculated based on 3-min Hb changes. The preoperative blood volume was extrapolated from the marked hemodilution occurring during the onset of cardiopulmonary bypass. Clinicaltrials.gov: NCT01115166. RESULTS: The distribution half-time of Ringer's acetate averaged 8 minutes, corresponding to a transcapillary escape rate of 0.38 ml/kg/min. The intravascular albumin mass increased by 5.4% according to mass balance calculations. The preoperative blood volume, as extrapolated from the drop in hemoglobin concentration by 32% (mean) at the beginning of cardiopulmonary bypass, was 0.6-1.2 L less than that estimated by anthropometric methods (p